2010
DOI: 10.1097/cnq.0b013e3181ecd56d
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Spirituality Into Critical Care

Abstract: Integration of the spiritual domain into the nursing plan of care positively influences health and wellness. Applying nursing theory to practice reinforces the advanced practice nurse's (APN's) responsibility to integrate spiritual care into the critical care environment. Indeed, all nurses have an obligation to integrate spiritual care because the focus of nursing care is beneficence. Moreover, the focus of APN care is not curing, but healing. Healing can be assisted by entering into the patient's suffering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…The topic of spirituality and spiritual care of patients has been included in nursing research for decades; however, current literature supports that nurses are feeling unprepared to provide this type of care. If spiritual assessment and care are an important element of holistic treatment of the patient, it is imperative that all nurses, including APRNs, feel confident and comfortable in providing this type of care (Chrash et al, 2011;Hubbell et al, 2006;Maddox, 2001;Weiland, 2010). Understanding the attitudes and knowledge of spirituality and spiritual care of APRN students may help graduate nursing education programs develop curriculum regarding the provision of spiritual care in nursing practice in the future.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The topic of spirituality and spiritual care of patients has been included in nursing research for decades; however, current literature supports that nurses are feeling unprepared to provide this type of care. If spiritual assessment and care are an important element of holistic treatment of the patient, it is imperative that all nurses, including APRNs, feel confident and comfortable in providing this type of care (Chrash et al, 2011;Hubbell et al, 2006;Maddox, 2001;Weiland, 2010). Understanding the attitudes and knowledge of spirituality and spiritual care of APRN students may help graduate nursing education programs develop curriculum regarding the provision of spiritual care in nursing practice in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It begs the question of whether spiritual assessments are actually being taught in nursing education programs. The literature pertaining to APRN education has also demonstrated that spiritual caregiving content is both required and necessary at the graduate level of nursing education, yet the inclusion of this important content has been neglected (Carron & Cumbie, 2011;Hubbell et al, 2006;Maddox, 2001;Stranahan, 2001;Tanyi, et al, 2009;Weiland, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations